The influence of intangible resources on the performance of Waqf project collaboration: mediating effect of sustainability and moderating role of collaborative effort / Siti Sara Ibrahim - Ibrahim, Siti Sara (2020)
The waqf institution has contributed significantly to sustainable socioeconomic growth. Despite its remarkable significance in this industry, waqf institution is still confronted with several industrial challenges, and one of them is the underperformance of waqf properties development that is caused by the lack of resources as well as an integrative approach. Resources management through cross-sector collaboration practices between the State Islamic Religious Councils (SIRCs) and their partners has been suggested for a better performance of waqf properties development. However, the claim was not supported empirically within the academic literature. In response to this issue, this thesis has examined the influence of intangible resources namely commitment, trust, networking and urgency on the performance of waqf project collaborations through the integration of the Resources Based View (RBV) theory and Stakeholder Salience theory. This thesis has also assessed the mediating effect of sustainability with regard to the relationship between commitment, trust, networking and urgency on the performance of waqf project collaborations. Finally, the present thesis has evaluated the moderating role of collaborative effort in strengthening the relationship between sustainability and performance which was argued to be inconsistent in previous literatures. A quantitative approach was conducted using a set of questionnaires that were distributed among the SIRCs and their partners based on the available waqf project collaborations. The research model was further analysed using the Partial Least Square-Structural Equation Modelling (PLS-SEM) technique. Based on the research questions, three core findings have been derived as follows: 1) commitment, trust, and urgency significantly influenced the performance of waqf project collaborations in Malaysia; on the other hand, networking was insignificant to the performance of waqf project collaborations; 2) as a mediating variable, sustainability partially mediated the relationship between trust, networking and urgency with performance. Contrastingly, commitment demonstrated an insignificant influence when tested indirectly through sustainability as a mediating variable; it was concluded to be a standalone influence on the performance of waqf project collaborations, and 3) as a moderating variable, collaborative effort played a significant role in strengthening the relationship between sustainability and performance in this study. This thesis contributes the relevant empirical evidence which indicates that intangible resources do play a significant role in influencing the performance of waqf properties development through cross-sector collaboration practices between the SIRCs and their partners. The research framework of this thesis has been registered for Intellectual Property Rights (IPR) to maximize excludability and increased innovativeness. Industry practitioners are encouraged to adopt this research framework in developing a model that can provides a comprehensive guideline on the importance of resources management. This implementation is crucial to enhance the performance of existing waqf properties development in the industry. Consequently, the significant role of waqf on the development of sustainable socioeconomic growth will be further enhanced.